The Influence of Social Capital on Social Well-Being through the Mediating Role of Quality of Life and Satisfaction with Life (Case Study: 18-30 Year Old Youth in Ghaen) - Mohammad hasan sharbatiyan; elmira erfanian ghasab (توسعه اجتماعی)
Increasing social well-being is one of the major concerns of any society. Identifying the factors affecting social well-being can lead to useful plans and strategies in this regard. In this paper, a model is constructed of important social variables such as social capital, quality of life, life satisfaction and social well-being. The population of the population is 18-30 years old in Ghaen city, South of Khorasan, with a sample size of 400 according to the Cochran formula. A randomized cluster sampling method was used for statistical analysis of standardized and researched questionnaires. The reliability and validity of the variables of the model are all in an acceptable level and the structural equation method was used to test the model with pls software; The results show that social capital, quality of life and life satisfaction affect social well-being, as well as quality of life and life satisfaction in the relationship between social capital and social welfare, mediating role.